Case Report: Eosinophilic esophagitis and hen's egg tolerance—two cases, treated with topical steroids, showing remission with highly heated but not less heated hen's egg - Nuyttens, Lisa; De Vlieger, Liselot; Ieven, Toon; Diels, Marianne; Bosmans, Tessa; Van Meerbeeck, Sara; Alliet, Tine; Dominicus, Toon; Hoffman, Ilse; Bullens, Dominique M. A. (Frontiers in Allergy, 2025)
Eosinophilic esophagitis (EoE) is a chronic, antigen-mediated disease characterized by eosinophilic inflammation of the esophagus. Common triggers in Europe include cow's milk, hen's egg, wheat, soy, (pea)nuts, and (shell)fish. Recent studies indicate that heated forms of cow's milk in cow's milk-induced EoE may be well tolerated. Similar to cow's milk, we present two cases of children with hen's egg-triggered pediatric EoE treated with topical steroids who remained in remission after the introduction of highly heated forms of hen's egg. The introduction of less heated forms, however, led to relapse. These two cases suggest that heated hen's egg may be well tolerated in hen's egg-induced pediatric EoE, potentially allowing for a less restrictive diet and improved quality of life. Further research is necessary to explore the potential for inducing tolerance to less heated and/or raw egg through the gradual introduction of heated egg products.